Knowledge and Awareness towards Dental Management of Post-Cardio-Thoracic Surgery Patients among Dental Students - Johara Maria Cruz; Keerthi Narayan. V; Vasumathi.D (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background of the Study: Oral health care professionals must be able to identify various cardiac diseasesand its associated post-operative dental emergencies to adopt the appropriate measures to treat themefficiently and effectively. A comprehensive dental treatment plan should be constructed keeping in view allthe possible complications related to the post-operative cardio-thoracic surgical factors.Aim: This study was aimed to determine the knowledge, attitude and awareness towards dental treatmentand their management following Cardio-thoracic surgeries among the dental students at undergraduate andpostgraduate level.Methodology: A cross sectional survey was conducted using self-administered questionnaires, throughGoogle forms among 100 dental students from Tamil Nadu India. Statistics has been done and results aretabulated.Results: The overall knowledge towards various cardio-thoracic surgical procedures carried out and theirdental management among dental students was only 65% and 45% for postgraduates and interns grouprespectively.Conclusion: The present study showed lack of awareness with limited knowledge and attitude towardsvarious cardiac-thoracic surgical procedures carried out and their corresponding dental management amongthe dental students especially at the undergraduate level. Hence enlightening and educating the students onseveral post-surgical management phases at the undergraduate level is essential for effective and efficienttreatment outcome and increase the quality of life.